SportsCenter : a case study of media framing U.S. sport as the COVID-19 epicenter - Bell, Travis R. (SAGE Business cases., 2021)
When COVID-19 enveloped sport, it presented SportsCenter, ESPN's primary news vehicle, with an unexpected and ironic form of "March Madness," with basketball as the sporting epicenter for a pandemic. This case study applied an ethnographic content analysis to examine how the cancellation or postponement of sport as a result of COVID-19 was framed across 22 episodes of SportsCenter from March 8 to 14, 2020. More than 134 min of coverage was devoted to COVID-19-related stories, and 268 unique types of stories were produced. Descriptive statistics suggested that COVID-19 was framed as having a direct impact on U.S. men's professional sports leagues and the National Collegiate Athletic Association men's basketball tournament. When considering news format characteristics, SportsCenter produced its coverage through convenience and relevance to ESPN, not sport. Even during a "breaking news" pandemic, SportsCenter retained its long-standing news process of gender bias and nationalistic favoritism. The visual difficulty of how to "show" coronavirus also presented a production challenge, but the messages and cues embedded in the visuals depicted a rapid shift in discourse that focused on basic reporting without health or global context. Instead, SportsCenter overwhelmed viewers with how sport was ripped away from (U.S.) American society.